Lawanen mga alaala ng pagkubkob : mga haraya ng pag-igpaw - Tiburon, Almayrah Abbas; Cura, Faye; Rival, Rae (Gantala Press, 2018)
Collection of literary works on result of the military action in Marawi, Philippines.